2014
DOI: 10.1016/j.ijfatigue.2013.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Micro-mechanical modelling of fretting fatigue crack initiation and wear in Ti–6Al–4V

Abstract: a b s t r a c tA micro-mechanical modelling methodology is presented for predicting fretting fatigue crack nucleation in Ti-6Al-4V. The methodology is based on a combination of (i) a unit cell crystal plasticity model of Ti6Al-4V, (ii) a frictional contact model of an experimental fretting wear configuration, and (iii) implementation of a microstructure-sensitive fatigue indication parameter for prediction of crack nucleation. A novel micro-mechanical method for wear prediction is presented. A key finding is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…In the context of fretting, McCarthy et al [15] found reasonable agreement between experimentally measured fretting fatigue lives and computationally predicted lives using . McCarthy et al [24] also highlighted the capability of accumulated plastic slip for prediction of wear in CP fretting models without the need for a user-defined wear rate. Accumulated plastic slip is calculated using the velocity gradient p :…”
Section: Fatigue Crack Initiationmentioning
confidence: 99%
“…In the context of fretting, McCarthy et al [15] found reasonable agreement between experimentally measured fretting fatigue lives and computationally predicted lives using . McCarthy et al [24] also highlighted the capability of accumulated plastic slip for prediction of wear in CP fretting models without the need for a user-defined wear rate. Accumulated plastic slip is calculated using the velocity gradient p :…”
Section: Fatigue Crack Initiationmentioning
confidence: 99%
“…It has been previously presented by the authors [17,18], but is briefly outlined here for completeness, particularly for definition of the key constitutive parameters. Plastic slip is assumed to obey Schmidt's law [22], where the rate of plastic shear strain, _ γ α , for a particular slip system, α, is assumed to depend on the resolved shear stress, τ α , through the following power law:…”
Section: Crystal Plasticity Calibrationmentioning
confidence: 99%
“…The key advantage of the method was the prediction capability of crack initiation location and scatter in the fatigue life. McCarthy et al [23][24][25] used the same FIP in the case of fretting fatigue of stainless steel 316L. The rate of accumulated plastic slip _ p can be calculated by the following equation:…”
Section: Fatigue Indicator Parametermentioning
confidence: 99%